KAJIAN PENYALAHGUNAAN NARKOBA DALAM PERSPEKTIF PENDIDIKAN AGAMA KRISTEN - Fredik Melkias Boiliu; Desetina Harefa; Dewi Lidya S; Ardianto Lahagu; Solmeriana Sinaga (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2021)
This article aims to discuss drug abuse in the perspective of Christian religious education. Narcotics are basically good drugs when used according to the dosage or doctor's recommendations for health. However, if someone uses it without medical indication or without a doctor's instructions because of the disease or other things recommended by the doctor, it will cause addiction / addiction and dependence popularly known as narcotics. In this case, without the indication (use) recommended by a doctor or an improper dose it will be dangerous to human health and can even cause sudden death. Bible neither directly addresses the topic of drug abuse nor mentions literal prohibition on narcotics and their use. However, it does not mean drug abuse is allowed. In Christian faith, believers must abstain from drugs because drugs can damage both physically and spiritually. In Corinthians 7: 1, it explains "purify yourselves from all things that can defile body and spirit, so that your position may be perfect in the fear of God". This means that as a Christian, he must protect and purify his body so that he does not sin. Thus, drugs can damage the body, both soul and mind, so drug use is not allowed. In this article, the author uses literature review and literature research methods, utilizing written ideas as a source of emphasis on the interpretation and analysis of the meaning of the.